Protocol for Rational Design of Covalently Interacting Inhibitors. Issue 15 (24th September 2014) - Schmidt, Thomas C.; Welker, Armin; Rieger, Max; Sahu, Prabhat K.; Sotriffer, Christoph A.; Schirmeister, Tanja; Engels, Bernd
Abstract The inhibition potencies of covalent inhibitors mainly result from the formation of a covalent bond to the enzyme during the inhibition mechanism. This class of inhibitors has essentially been ignored in previous target‐directed drug discovery projects because of concerns about possible side effects. However, their advantages, such as higher binding energies and longer drug‐target residence times moved them into the focus of recent investigations. While the rational design of non‐covalent inhibitors became standard the corresponding design of covalent inhibitors is still in its early stages. Potent covalent inhibitors can be retrieved from large compound libraries by covalent docking approaches but protocols are missing that can reliably predict the influence of variations in the substitution pattern on the affinity and/or reactivity of a given covalent inhibitor. Hence, the wanted property profile can only be obtained from trial‐and‐error proceedings. This paper presents an appropriate protocol which is able to predict improved covalent inhibitors. It uses hybrid approaches, which mix quantum mechanical (QM) and molecular mechanical (MM) methods to predict variations in the reactivity of the inhibitor. They are also used to compute the required information about the non‐covalent enzyme–inhibitor complex. Docking tools are employed to improve the inhibitor with respect to the non‐covalent interactions formed in the binding site.